theory Height
imports "../Nominal2"
begin
text {*
A small problem suggested by D. Wang. It shows how
the height of a lambda-terms behaves under substitution.
*}
atom_decl name
nominal_datatype lam =
Var "name"
| App "lam" "lam"
| Lam x::"name" l::"lam" bind x in l ("Lam [_]._" [100,100] 100)
text {* Definition of the height-function on lambda-terms. *}
function
height :: "lam \<Rightarrow> int"
where
"height (Var x) = 1"
| "height (App t1 t2) = (max (height t1) (height t2)) + 1"
| "height (Lam [a].t) = (height t) + 1"
apply(rule_tac y="x" in lam.exhaust)
apply(simp_all)[3]
apply(simp add: lam.eq_iff)
apply(simp add: lam.distinct)
apply(simp add: lam.distinct)
apply(simp add: lam.eq_iff)
apply(simp add: lam.distinct)
apply(simp add: lam.eq_iff)
sorry
termination
apply(relation "measure size")
apply(simp_all add: lam.size)
done
text {* Definition of capture-avoiding substitution. *}
function
subst :: "lam \<Rightarrow> name \<Rightarrow> lam \<Rightarrow> lam" ("_[_::=_]" [100,100,100] 100)
where
"(Var x)[y::=t'] = (if x=y then t' else (Var x))"
| "(App t1 t2)[y::=t'] = App (t1[y::=t']) (t2[y::=t'])"
| "\<lbrakk>atom x \<sharp> y; atom x \<sharp> t'\<rbrakk> \<Longrightarrow> (Lam [x].t)[y::=t'] = Lam [x].(t[y::=t'])"
apply(case_tac x)
apply(simp)
apply(rule_tac y="a" and c="(b, c)" in lam.strong_exhaust)
apply(simp_all)[3]
apply(blast)
apply(blast)
apply(simp add: fresh_star_def fresh_Pair)
apply(blast)
apply(simp add: lam.eq_iff)
apply(simp add: lam.distinct)
apply(simp add: lam.distinct)
apply(simp add: lam.eq_iff)
apply(simp add: lam.distinct)
apply(simp add: lam.eq_iff)
sorry
termination
apply(relation "measure (size o fst)")
apply(simp_all add: lam.size)
done
text{* The next lemma is needed in the Var-case of the theorem below. *}
lemma height_ge_one:
shows "1 \<le> (height e)"
apply(nominal_induct e rule: lam.strong_induct)
apply(simp_all)
done
text {*
Unlike the proplem suggested by Wang, however, the
theorem is here formulated entirely by using functions.
*}
theorem height_subst:
shows "height (e[x::=e']) \<le> ((height e) - 1) + (height e')"
proof (nominal_induct e avoiding: x e' rule: lam.strong_induct)
case (Var y)
have "1 \<le> height e'" by (rule height_ge_one)
then show "height (Var y[x::=e']) \<le> height (Var y) - 1 + height e'" by simp
next
case (Lam y e1)
have ih: "height (e1[x::=e']) \<le> ((height e1) - 1) + (height e')" by fact
moreover
have vc: "atom y \<sharp> x" "atom y \<sharp> e'" by fact+ (* usual variable convention *)
ultimately show "height ((Lam [y].e1)[x::=e']) \<le> height (Lam [y].e1) - 1 + height e'" by simp
next
case (App e1 e2)
have ih1: "height (e1[x::=e']) \<le> ((height e1) - 1) + (height e')"
and ih2: "height (e2[x::=e']) \<le> ((height e2) - 1) + (height e')" by fact+
then show "height ((App e1 e2)[x::=e']) \<le> height (App e1 e2) - 1 + height e'" by simp
qed
end